MOTIVATING GENERATION Z TO EMBRACE ENGLISH THROUGH EDUCATION AND SURVEY - Murti, Fiqih Kartika; Lutfiani, Ayumi Septiana; Nabilah, Deshinta Jihan; Oktaviani, Dea; Rachmawati, Siti (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
The purpose of the implementation of PkM was to increase students’ motivation and awareness of the importance of English in real life, especially for vocational high school students who think English is just beneficial in school. To fix this problem, 35 students took part in an interactive motivational workshop. The lesson focused on how English is used in real life for things like digital communication, job interviews, and business documents. A question-and-answer session followed to encourage active participation. After the session, a 25-question survey was distributed to assess the students’ change in motivation and perception. The PkM was held at SMK An Nur Slawi, a vocational high school located in Tegal Regency, Central Java, Indonesia. The results showed a significant improvement in students’ understanding of the role of English in professional and daily life. Many of them said they were more interested in using English outside of class and felt more confident doing so. Documentation and participant feedback indicated a highly positive and engaged atmosphere during the session. The results imply that using emotionally engaging methods to link learning English to students’ future professional aspirations can boost their long-term motivation. Other vocational high schools can use this methodology of teaching English to help students learn the language in a way that is more useful and meaningful.